Natūrfilosofinės subjekto ir gamtos apibrėžtys: F. W. J. Schellingas ir I. H. Grantas - Junelis, Domas (Problemos, 2024)
This article examines the notions of subject and nature as well as their relationship in F. W. J. Schelling’s naturephilosophy (Naturphilosophie), primarily based on the contemporary interpretation provided by I. H. Grant. It is explained that naturephilosophy, which treats the subject as produced by nature, and nature itself as absolute productivity, at the same time critically reacts against the inclination of I. Kant’s transcendental idealism to hypostasize the subject by separating it from nature. The article argues that naturephilosophy comes close to materialist logic, according to which, the subject, being the product of nature’s productivity, is one of the nature’s moments, and therefore its pretentions to once and for all define nature are doomed to fail. This indeterminacy is not the effect of epistemological lack, but the ontological condition of nature and its products.